Recomendações de boas práticas para apps de serviço de atendimento bancário à pessoa idosa - Mota, Suzan Evellyn Nascimento da (Brasil, 2024)
With the advancement of technology, mobile devices are becoming common in users' daily lives, due to the practicality and mobility they offer. In this context, the integration of banking services into the digital environment becomes evident. However, in the development of these new applications, it is common for some groups, such as the elderly, to have their needs met, which can result in digital exclusion for this population. Considering the aging of the Brazilian population, it is crucial to consider the physical and psychological factors of the elderly in these tools. This study aims to establish good practices to reduce the gap between older people and their interaction with banking applications. To this end, a theoretical study was conducted on aging, digital accessibility and user experience. The methodology is based on Archer’s (1964) three phases. In the Analytical Phase, the interfaces of well-known banks on the market were proven by a heuristic evaluation and the profile of the target audience was identified through interviews and questionnaires. In the Creative Phase, personas were edited with the profiles found, preparation for the usability test and definition of evaluation criteria. In the Executive Phase, we carried out the usability test, an analysis based on the established criteria and data tabulation. As a result, ten good practices were identified that facilitate the use of banks by elderly people, to promote autonomy, performance and confidence.